(untitled) (Research, Society and Development, 2020)
Introduction: Bruxism is defined as a parafunctional chewing activity characterized by the clenching and / or grinding of teeth that occurs both during sleep and during the surveillance period. Methods: Thirty female patients between 18 and 40 years old who had bruxism and orofacial pain were selected and randomized into two groups: control group (n = 15), where individuals received 0.05 ml of sterile saline solution that was applied to the bundle anterior temporal muscles and 0.2 ml for each masseter muscle, and an experimental group (n = 15), individuals received 20 units of A-botulinum toxin (Botox®) applied to each masseter muscle and 5 units of A-botulinum toxin applied to the anterior bundle of each temporal muscle. Patients were called back for reevaluation every thirty days. At these moments, they underwent an evaluation of the load force and electromyography. Results: At 30, 60, 90 and 120 days, a decrease in electromyographic activity was observed in the A-botulinum toxin group (p <0.001). In the experimental group, the left masseter muscle showed no significant difference between the variable load cell and time (p = 0.968), nor between electromyography versus load (p = 0.072), with a statistically significant difference between time and electromyography. (coef = 0.322; p <0.001). Conclusion: The intramuscular application of botulinum toxin type A in patients with bruxism has proved to be an effective method for hyperactivity of the masseter muscle in patients with bruxism, improving and decreasing the levels of muscle contraction.